C1QBP promotes apoptosis of goat fetal turbinate cells via inhibiting the expression of TRIM5 or TNFSF10 - Li, Qiuyun; Tang, Zhengding; Xiang, Hua; Dan, Yixin; Ren, Yupeng; Zhang, Huanrong; Yang, Falong; Zhu, Jiangjiang (Frontiers in Veterinary Science, 2025)
BackgroundInfectious ecthyma is a severe and highly contagious disease caused by ORF virus (ORFV). The virus is responsible for significant economic losses in the goat industry and threatens humans. Regarding complement component 1, q subcomponent binding protein (C1QBP), we previously showed that C1QBP can interact with ORFV129. However, the role of C1QBP in regulating the apoptosis of goat fetal turbinate cells is unknown.MethodsAfter pcDNA3.1-C1QBP and siRNA were transfected into goat fetal turbinate cells (GFTCs), the expression of C1QBP was detected by western blot and cell cycle and apoptosis using flow cytometry. The expression of cycle-related genes cyclin-dependent protein kinase 2 (CDK2) and cyclin-dependent kinase inhibitors 1A (p21) and apoptosis-related genes cysteinyl aspartate specific proteinase 3 (Caspase 3), cysteinyl aspartate specific proteinase 7 (Caspase 7), p53, poly (ADP-ribose) polymerase 1 (PARP1), B-Cell lymphoma-2 Like-11 (BCL2L11), B-cell lymphoma 2 associated X protein (Bax), and B-cell lymphoma 2 (Bcl-2) were tested by real-time quantitative PCR (RT-qPCR). The effect of MTT on the proliferation of GFTCs was detected. The localization of C1QBP in GFTCs was detected by inverted fluorescence microscope. Finally, transcriptome sequencing was performed and validated by siRNA treatment knockdown of C1QBP, and screening two genes tripartite motif containing 5 (TRIM5) and tumor necrosis factor superfamilymember10 (TNFSF10) with significant changes in expression levels and relevance to cell apoptosis, and to verify their roles in C1QBP-induced cell apoptosis.ResultsKnockdown of C1QBP significantly increased cell viability; cells remained in the G0/G1 phase and reduced apoptosis. Knockdown of C1QBP reduced the mRNA expression of CDK2, p21, Caspase3, Caspase7, Bax, PARP1, BCL2L11, and p53, up regulated the mRNA expression of the Bcl-2. Except for Bcl-2, The opposite effect was observed when C1QBP was overexpressed in GFTCs and the mRNA levels of Bcl-2 had no significant effect. Immunostaining revealed intracellular localization of C1QBP, primarily in the cytoplasm of the GFTCs. Furthermore, gene expression profiling analysis in C1QBP depleted cells compared to the control revealed that a total of 236 differential expression genes (DEGs), including 119 up regulated DEGs and 117 down regulated DEGs, and the expression of TRIM5 and TNFSF10 genes were significantly upregulated. Pathway analysis were predicted to be enriched in Herpes simplex virus 1 infection, Pathways in cancer, PI3K-Akt signaling pathway, Apoptosis, Apoptosis-multiple species and p53 signaling pathway. C1QBP reduced the expression of TRIM5 and TNFSF10 genes. Knockdown of TRIM5 promoted apoptosis in GFTCs, but silencing of TNFSF10 had no change in apoptosis rate. In particular, the apoptosis rate was significantly increased in the TRIM5-siRNA2 or TNFSF10-siRNA2 and C1QBP-siRNA2 group compared to the only C1QBP-siRNA2 group.ConclusionThese findings provide a deeper understanding of the role of C1QBP in apoptosis and could pave the way for further study investigating the role and mechanism of C1QBP protein in mediating the regulation of cell apoptosis by ORFV.